Analisis Pengaruh Kualitas Pelayanan, Ketepatan Waktu Pengiriman, Dan Harga Terhadap Kepuasan Pelanggan Pada Ninja Expres Kota Payakumbuh - Habibbullah Rizki; Syuryatman Desri; Laila Hasanah; Muhammad Ihsan (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
This research discusses the analysis of the influence of service quality, on time delivery, price on customer satisfaction at Ninja Express Payakumbuh City. The aim of this research is to determine the effect of service quality, timeliness of delivery and price on customer satisfaction with package delivery services by Ninja Express in Payakumbuh City. The method used is quantitative. Data was collected through a survey with a questionnaire. This questionnaire was shown to the people of Payakumbuh city who had used the Ninja Xpress expedition. Samples were taken as many as 100 people. The technique used is non-probability sampling with a purposive approach. This research uses multiple regression analysis. From this research, it was found that 37.5% of Ninja Express service quality in Payakumbuh influences customer satisfaction, 38.5% of delivery accuracy influences customer satisfaction, and 23.3% of price perception influences customer satisfaction with Ninja Express.